2009
DOI: 10.1016/j.neuroimage.2008.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Automated mapping of hippocampal atrophy in 1-year repeat MRI data from 490 subjects with Alzheimer's disease, mild cognitive impairment, and elderly controls

Abstract: As one of the earliest structures to degenerate in Alzheimer's disease (AD), the hippocampus is the target of many studies of factors that influence rates of brain degeneration in the elderly. In one of the largest brain mapping studies to date, we mapped the 3D profile of hippocampal degeneration over time in 490 subjects scanned twice with brain MRI over a 1-year interval (980 scans). We examined baseline and 1-year follow-up scans of 97 AD subjects (49 males/48 females), 148 healthy control subjects (75 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
188
5
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 103 publications
17
188
5
1
Order By: Relevance
“…In line with the strong and consistent results for APOE when using LOAD as the phenotype, most T-1 weighted MRI studies reported an association of APOE e4 with accelerated LOAD-related volume loss in the hippocampal region. [53][54][55][56] This is supported by several studies exploring the effect of the APOE e4 allele on glucose metabolism using FDG-PET, [57][58][59][60] or amyloid deposition using ([¹¹C] PiB-PET. [61][62][63] Few studies have examined the association between other genes and LOAD imaging measures, and most of these were GWAS studies.…”
Section: Genetic Variation and Neuroimaging Measures In Loadmentioning
confidence: 73%
“…In line with the strong and consistent results for APOE when using LOAD as the phenotype, most T-1 weighted MRI studies reported an association of APOE e4 with accelerated LOAD-related volume loss in the hippocampal region. [53][54][55][56] This is supported by several studies exploring the effect of the APOE e4 allele on glucose metabolism using FDG-PET, [57][58][59][60] or amyloid deposition using ([¹¹C] PiB-PET. [61][62][63] Few studies have examined the association between other genes and LOAD imaging measures, and most of these were GWAS studies.…”
Section: Genetic Variation and Neuroimaging Measures In Loadmentioning
confidence: 73%
“…This contrasts with the rates of only 1-2% per year in normal subjects (aged around 70-80 years) (9,10,11). This disease-related difference offers a potential measure which can be used to provide evidence for disease modification.…”
Section: Regional Measures: Hippocampusmentioning
confidence: 86%
“…Most trials have used manual outlining of the hippocampus; more recently semi-automated measures have been used -some of these require landmarks to be placed around the hippocampus from which an algorithm delineates the hippocampal boundaries. Fully automated (template-based) measures have also been developed but have not to date been used in large trials (3,10).…”
Section: Regional Measures: Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, patients with AD have abnormally high rates of brain atrophy [Apostolova et al, 2006;Callen et al, 2001;Leow et al, 2009]. Additionally, brain atrophy may be detectable on MRI even before cognitive impairment is clinically evident, as demonstrated in a study showing greater atrophy in asymptomatic APOE4 carriers compared to non-carriers [Morra et al, 2009]. …”
Section: Introductionmentioning
confidence: 99%